Ways of Implementing the Design of the Individual Education Trajectory of the Future Primary Class Teachers - BotIrova Nasiba Djurabayevna (Zien Journals, 2023)
In this article, the importance of the personal development approach in the development of the problems of pedagogical design of the individual trajectory of the development of educational competence in future teachers is considered.
Keywords: Learning competence; methodological; pedagogical design